2022
DOI: 10.1155/2022/8929058
|View full text |Cite|
|
Sign up to set email alerts
|

Effect of Tegretol on Oxidative Stress, Serum Inflammatory Factors, and Left Ventricular Function in AMI Patients after Emergency PCI

Abstract: To investigate the effects of tegretol on oxidative stress, serum inflammatory factors, and left ventricular function in patients with acute myocardial infarction (AMI) after emergency percutaneous coronary intervention (PCI), 70 AMI patients who received PCI in the emergency department of our hospital from January 2021 to December 2021 were collected. The patients in the control group were treated with aspirin, clopidogrel, and heparin sodium during the perioperative period, and the patients in the study grou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 13 publications
(11 reference statements)
0
3
0
Order By: Relevance
“…However, some patients may experience ventricular remodeling after PCI, with related nerves activated, increased inflammation response, leading to complications such as pneumonia and heart failure, which can also pose a threat to patients' health. 14,15 At present, T-ProBNP, GDF15 and other biomarkers commonly used in clinical practice are susceptible to multiple factors such as autoimmune system disorders and inflammation, and the prediction accuracy is low. 16 Therefore, it is particularly important to find specific factors that can assist in diagnosis and prediction of the prognosis of patients with acute myocardial infarction.…”
Section: Dovepressmentioning
confidence: 99%
“…However, some patients may experience ventricular remodeling after PCI, with related nerves activated, increased inflammation response, leading to complications such as pneumonia and heart failure, which can also pose a threat to patients' health. 14,15 At present, T-ProBNP, GDF15 and other biomarkers commonly used in clinical practice are susceptible to multiple factors such as autoimmune system disorders and inflammation, and the prediction accuracy is low. 16 Therefore, it is particularly important to find specific factors that can assist in diagnosis and prediction of the prognosis of patients with acute myocardial infarction.…”
Section: Dovepressmentioning
confidence: 99%
“…Acute myocardial infarction (AMI) results in ventricular remodeling in response to oxygen demand, which is characterized by left ventricular dilatation and elevated myocardial wall stress [1,2]. Percutaneous coronary interven-tion (PCI) has been regarded as a gold standard therapy for AMI therapy to restore coronary blood flow [3,4]. AMI is a frequent reason for fatality in patients with type 2 diabetes mellitus (T2DM) and vascular dysfunction is a main ingredient of diabetic cardiomyopathy [5].…”
Section: Introductionmentioning
confidence: 99%
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [1]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process:…”
mentioning
confidence: 99%
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [ 1 ]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process: Discrepancies in scope Discrepancies in the description of the research reported Discrepancies between the availability of data and the research described Inappropriate citations Incoherent, meaningless and/or irrelevant content included in the article Peer-review manipulation …”
mentioning
confidence: 99%